Experimental characterization and comparison of automobile brake linings - Topuz, Polat (CARL HANSER VERLAG, 2019)
In this study, characteristics of automobile disc brake linings produced by three different manufacturers were compared experimentally, these being original parts (OEM), subsidiary industrial production parts (SIPM), and brake linings of Turkish production (TM). These brake linings which vary in composition, components, wear and friction characteristics, as well as mechanical and physical properties were investigated. In addition, their environment and their usage were compared. For the ensuant chemical analyses, scanning electron microscopy (SEM), EDS (energy dispersive spectroscopy) system and XRF (X-ray fluorescence) were used. TG (thermo gravimetric analysis) was performed to determine the mass losses in the brake lining materials. Wear friction tests of the brake linings carried out according to the JIS D 4411 standard. Apart from these, the hardness, density and internal shear strength values of the brake linings were measured.
Keywords: Automobile brake linings; composition; wear; friction; environment; Materials Science